The Dairy Value Chain, Inclusive Business Model, and Inclusiveness Improvement of Southern Bandung Dairy Cooperative (KPBS) Pangalengan - Annisa Ramadanti; Arief Daryanto; Sukardi Sukardi (School of Business, Bogor Agricultural University (SB-IPB), 2017)
There is an opportunity for smallholder dairy farmers to grow in meeting the increasing demand of milk and milk products in Indonesia. IBM is a suitable method for smallholder improvement. KPBS Pangalengan is one good example of institution which implements IBM. This research aims to analyze KPBS Pangalengan’s current dairy value chain, business model, inclusiveness, as well as the possible areas of improvement for its inclusiveness respectively using VCM, BMC, and NBM Principles. Based on the result of this research, there is a tendency of declining fresh milk production in dairy farmer level and a tendency of Milk Processing Industry (MPI) as the chain leaders due to their domination along the chain. Other customer perspective business models have their most weaknesses. The weakest area of KPBS Pangalengan inclusiveness is measurement of outcome area. The four areas of improvement for KPBS Pangalengan inclusiveness include fresh milk production area, IT support area for the downstream side, potential diversifications area (agritourism and milk café concept), and measurement of outcome area. Keywords: inclusiveness, KPBS Pangalengan, Milk Processing Industry, smallholders, value chain